2022
DOI: 10.3390/ejihpe12070051
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Psychometric Properties of the ILO-WHO Workplace Stress Scale: A Study with Workers from the Canary Islands

Abstract: Occupational stress, as a negative facet, is a pervasive problem with significant implications for organizations, employees, welfare systems and health. The implementation of measurement tools that can capture the different organizational dimensions that determine stress in workers is part of the stress management and troubleshooting strategy that every company must manage daily. The aim of the present study was to adapt and validate the 25-item version of the ILO-WHO stress scale by Ivancevich and Matteson in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Previous results showed that insight orientation meditates the associations between personality traits and a prominent variable involved in maintaining the balance between job demands and job resources: job crafting (Gori et al, 2021b). Thus, the enhancement of insight orientation can lead workers to the achievement of new awareness about cognitive, emotional and social aspects relevant to facilitate job crafting with the aim of also reducing workplace stress (Ramaci et al, 2019;Caponnetto et al, 2022;Torvisco et al, 2022). Furthermore, job crafting emerged in the literature as a positive variable associated with a large array of well-being and positive organizational outcomes also in vulnerable workers (Svicher and Di Fabio, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Previous results showed that insight orientation meditates the associations between personality traits and a prominent variable involved in maintaining the balance between job demands and job resources: job crafting (Gori et al, 2021b). Thus, the enhancement of insight orientation can lead workers to the achievement of new awareness about cognitive, emotional and social aspects relevant to facilitate job crafting with the aim of also reducing workplace stress (Ramaci et al, 2019;Caponnetto et al, 2022;Torvisco et al, 2022). Furthermore, job crafting emerged in the literature as a positive variable associated with a large array of well-being and positive organizational outcomes also in vulnerable workers (Svicher and Di Fabio, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the IWPQ, even with the elimination of one item, presents an excellent performance that can also be used in the Italian context, and given the scarcity of validated instruments in the Italian context, it may prove to be a useful tool and an excellent indicator of the success and well-being of organisations and the people who work in them. Studies such as this underline the importance of having standardised instruments for measuring important constructs such as the IWP that are valid in different contexts (e.g., Public Administration, Health Care sector) that allow comparisons to be made across countries and can help research and practise learn more about, for example, the important antecedents and consequences of individual job performance [69][70][71][72].…”
Section: Discussionmentioning
confidence: 99%
“…The goodness of fit indices for all constructs was >0.90, and scale reliability for all measurement items was also >0.90 except for work-life enhancement, which was 0.88. The work stress scale was adapted from the Work Stress Scale developed by Torvisco et al [ 86 ]. The 25-item scale developed based on World Health Organization and International Labor Organization guidelines contained 25 items, of which anxiety and adverse effects on health and well-being were assessed in this study.…”
Section: Methodsmentioning
confidence: 99%